Work ability following breast cancer – the MyHealth randomized controlled trial - Trine A. Horsbøl; Lena Saltbæk; Caroline Urhammer; Randi V. Karlsen; Christoffer Johansen; Pernille E. Bidstrup; Beverley L. Høeg; Vibeke Zoffmann; Federica Belmonte; Ingelise Andersen; Anne S. Friberg; Mads N. Svendsen; et al. (Acta Oncologica)
Background and purpose: We previously demonstrated positive effects on quality of life and mental health following breast cancer when comparing a nurse-led follow-up program without scheduled visits (MyHealth) to regular follow-up. This study aims to examine whether MyHealth also positively impacts self-reported work ability.